Serum DHEA-S increases in dogs naturally infected with Ehrlichia canis - Rondelli, M. C. H. [UNESP]; Munhoz, T. D.; Catandi, P. B.; Freschi, C. R. [UNESP]; Palacios Junior, R. J. G.; Machado, R. Z. [UNESP]; Tinucci-Costa, M. [UNESP] (Elsevier B.V., 2015)
Adrenocortical disturbances are expected in canine ehrlichiosis due to the immunological challenges caused by infection and consequent inflammation. Thus, this study aimed to evaluate the occurrence of adrenocortical hormonal alterations in dogs naturally infected with Ehrlichia canis (n=21) as positively confirmed by the presence of anti-E. cartis antibodies (Dot-ELISA) and nested PCR (nPCR). Serum dehydroepiandrosterone sulfate (DHEA-S) concentrations were assessed via ELISA before and one hour after ACTH stimulation. Another 10 healthy dogs were subjected to the same stimulation protocol and used as controls. The results revealed that baseline and post-ACTH DHEA-S concentrations were significantly greater in sick dogs, regardless of gender, and this finding illustrates the stress induced by naturally acquired ehrlichiosis in dogs. (C) 2015 Elsevier Ltd. All rights reserved.
Keywords: Dogs; Ehrlichia canis; Adrenal; DHEA-S; Stress